Medication Therapy Management and Preconception Care: Opportunities for Pharmacist Intervention - Natalie A. DiPietro; David R. Bright (University of Minnesota Libraries Publishing, 2014)
As medication therapy management (MTM) continues to grow in the profession of pharmacy, careful consideration as to areas for positive patient impact is warranted. Given the current gaps in preconception care in the United States, and the accessibility and expertise of the pharmacist, MTM interventions related to preconception care may be valuable. This paper describes potential for pharmacist intervention in several different areas of preconception care. Notably, targeted medication reviews may be appropriate for interventions such as folic acid recommendations, teratogenic/category X medication management, immunizations, and disease state management. Comprehensive medication reviews may be warranted for selected disease states due to complexity of interventions, such the management of diabetes. Comprehensive medication reviews may also be warranted if several targeted interventions are necessary, or if there are a several medications or disease states requiring intervention. Pharmacists also have important roles in screening, support, and referrals needed for preconception care in the context of MTM. Patients may benefit substantially from pharmacist-directed MTM services related to preconception care. In addition, depending on clinical pharmacy service contracts and billing opportunities, pharmacists may be reimbursed for providing these services, generating sustainable revenue while fulfilling an important public health need.   Type: Idea Paper